AKTIVITAS ANTIBAKTERI DAN ANTI-UV BEBERAPA ASCIDIAN DARI PERAIRAN PANGALISANG BUNAKEN - Yuliana Macpal; Veibe Warouw; Deiske A Sumilat; James J.H. Paulus; Natalie D.C. Rumampuk; Reni L. Kreckhoff (JURNAL PESISIR DAN LAUT TROPIS, 2019)
Ascidians are sesile marine invertebrates that have bioactive compounds such as antibacterial and anti-UV. The purpose of this study is to determine the antibacterial activity against Escherichia coli and Staphylococcus aureus bacteria and to test the anti-UV activity of the ascidian water fraction. Antibacterial activity test was carried out using the diffusion method (disc diffusion Kirby & Bauer) and the water fraction of ascidian that showing antibacterial activity tested in a UV spectrophotometer to see the anti-UV activity. Results of the study were obtained 4 types of ascidians extracted from partitioned into water fraction, n-hexane fraction, methanol fraction. All three fractions were tested for antibacterial activity and the result showed that there were antibacterial activities of ascidian extract Clavelina sp. against both test bacteria with inhibition of S. aureus and E. coli with strong categories. Ascidian Phlebobranch sp. showed the presence of antibacterial activity with inhibition of S. aureus and E. coli with very strong categories (16,6 mm). extract Eudistoma sp. showed the presence of antibacterial activity with inhibition S. aureus and E. coli in the medium category (9 mm). The water fraction found active in antibacterial testing is then tested using a UV spectrophotometer for anti UV testing, the result show that water fraction of the four ascidians can absorb UV-B (290-320nm) and UV-A ( 320-400nm).Keywords : Ascidian, Antibacterial, Partition, Anti- UV.